2018
DOI: 10.7556/jaoa.2018.061
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Osteopathic Cranial Manipulative Medicine as an Adjunct to Conventional Postconcussion Symptom Management: A Pilot Study

Abstract: Osteopathic cranial manipulative medicine was considered a safe adjunctive treatment option to improve concussion-related symptoms and recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In a follow-up study by Dreyer et al, these techniques again found favorable trends in ICP, CPP, and outcomes when using OMT [ 29 ]. Patel and Sabini demonstrated that cranial OMT was a safe and effective adjunct in the treatment of concussions [ 30 ].…”
Section: Reviewmentioning
confidence: 99%
“…In a follow-up study by Dreyer et al, these techniques again found favorable trends in ICP, CPP, and outcomes when using OMT [ 29 ]. Patel and Sabini demonstrated that cranial OMT was a safe and effective adjunct in the treatment of concussions [ 30 ].…”
Section: Reviewmentioning
confidence: 99%
“…Neither study mentioned the duration of OMT. Patel and Sabini demonstrated that cranial OMT administered for four weeks was a safe and effective adjunct that reduces post concussive symptoms and accelerates recovery [21]. OMT-induced reduction in ICPs is thought to occur via increased CSF outflow from the cranial cavity in addition to improving glymphatic flow and decreasing interstitial brain edema [21].…”
Section: Osteopathic Manipulative Treatment To Improve Glymphatic Funmentioning
confidence: 99%
“…Concussion, which by definition meets the criteria as a minor TBI, can similarly be treated using these OMT techniques. As concussions have been linked to increased brain edema, improving glymphatic function may similarly decrease edema, and promote clearance of toxic metabolites actively being investigated as markers for TBI [9,21]. Being relatively quick and effective, OMT can supplement the treatment of concussions to great effect.…”
Section: Osteopathic Manipulative Treatment In Post Concussive Treatmentmentioning
confidence: 99%
“…18 Osteopathic manipulative treatment has been shown to yield significant improvement in symptoms associated with concussion, such as headache and vertigo. 18,19 Additionally, craniosacral therapy and visceral and neural manipulation have produced significant improvement in pain, cervical range of motion, and memory in former professional football players. 20 Recent research also demonstrates the safety of osteopathic cranial manipulative medicine in the treatment of patients with concussion.…”
Section: Osteopathic Structural Examinationmentioning
confidence: 99%
“…20 Recent research also demonstrates the safety of osteopathic cranial manipulative medicine in the treatment of patients with concussion. 19…”
Section: Osteopathic Structural Examinationmentioning
confidence: 99%